KEBIJAKAN PUBLIK DAN RITEL MODERN : STUDI KASUS PELAKSANAAN KEBIJAKAN PLASTIK BERBAYAR - Saraswaty, Amrita Nugraheni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study aims to determine the economic impact on the modern retail businesses after the application of public policy about plastic bag fee by the government. The methodology used is descriptive with interviewing 53 samples of modern retailer in Badung and Denpasar area. This study get the result that, in terms of modern retail, there is a tendency not to impose tariffs on consumer plastic bags because they do not want to lose customers. It can be concluded that the modern retail stores do not feel any significant change of the economic policy of plastic bags fee. Consumers are still willing to pay the price set by the government, and most of the modern retail stores choose not to implement a policy of that paid plastic. Going forward, the policy paid plastic can be equipped with alternative materials usage policies for shopping bags also with a higher tariff for plastic bags. So the number of plastic bags that are used can be reduced and replaced with environmentally friendly materials.